Multiple morphologies and functionality of nanowires made from earth-abundant zinc phosphide. Issue 2 (15th October 2019) - Escobar Steinvall, Simon; Tappy, Nicolas; Ghasemi, Masoomeh; Zamani, Reza R.; LaGrange, Thomas; Stutz, Elias Z.; Leran, Jean-Baptiste; Zamani, Mahdi; Paul, Rajrupa; Fontcuberta i Morral, Anna
Abstract : Semiconductors made of earth-abundant elements, such as zinc phosphide, have the potential to substitute less abundant, highly functional compound semiconductors such as InAs or InP. Abstract : Semiconductors made of earth-abundant elements, such as zinc phosphide, have the potential to substitute less abundant, highly functional compound semiconductors such as InAs or InP. Compound semiconductors in the form of nanowires could revolutionise application areas such as energy harvesting and optoelectronics. Here we synthesise Zn3 P2 nanowires tailored in four different morphologies, namely vertical, straight-titled, zigzag and crawling. The optical properties elucidated by cathodoluminescence spectroscopy indicate a shape and V/II ratio dependence. Band-edge, defects, or surface nanoclusters mediate the luminescence in different degrees. This work opens new avenues for the use of earth-abundant Zn3 P2 nanowires in photovoltaic applications.